Ребята, помогите с решением, пожалуйста! sin(п/6+t)cos(п/3-t)+sin(2п/3+t)sin(п/3-t)
Sin(п/6+t)cos(п/3-t)+sin(2п/3+t)sin(п/3-t)=sin(п/6+t)cos(п/3-t)+sin(п-п/3+t)sin(п/3-t)=sin(п/6+t)cos(п/3-t)+sin(п/3-t)sin(п/3-t)=sin(п/2-(п/3-t))cos(п/3-t)+sin(п/3-t)sin(п/3-t)=cos(п/3-t)cos(п/3-t)+sin(п/3-t)sin(п/3-t)=1
sin(п/6+t)cos(п/3-t)+sin(2п/3+t)sin(п/3-t)=sin(п/6+t)cos(п/3-t)+sin(п-(п/3-t))sin(п/3-t)=sin(п/6+t)cos(п/3-t)+sin(п/3-t)sin(п/3-t)=sin(п/2-(п/3-t))cos(п/3-t)+sin(п/3-t)sin(п/3-t)=cos(п/3-t)cos(п/3-t)+sin(п/3-t)sin(п/3-t)=1